Komunikasi Data Menggunakan Topologhy Tree dalam Pembelajaran Sistem Jaringan dan Telekomunikasi - Sabrina Nadya Octaviani; Raihan Raihan; Muhammad Irfan Andrianto; Muhammad Rifki Arrosyid; Didik Ariwibowo (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to find out how data communication uses tree topology in studying network and telecommunications systems. Computer networks have a very important role in communication and data sharing needs in this modern era. Communication network also means the connection of two or more separate computer systems, through this communication media the general public can communicate with each other using various resources. Data communication is the process of sending information between two points using binary code by passing through transmission channels and also switching or network equipment on computers between other computers, computers and terminals or other equipment. Communication occurs when there is a source and a goal. The data sent is information in the form of bits (0 and 1). Data are facts or parts of facts that contain meaning, which are connected to reality, symbols.